Educatorsâ€™ Perception of the Utilization of Information and Communication Tecnology (ICT) in Chemistry Learning - Hairida Hairida; Rahmat Rasmawan; Rody Putra Sartika; Masriani Masriani (Jurnal Penelitian Pendidikan IPA, 2023)
The use of ICT in education in the 21st century has facilitated educators to make changes in learning, so that learning becomes challenging and fun. This study aims to describe the perception of teachers regarding the use of information and communication technology in chemistry learning. For this purpose, a survey was conducted to collect data from 20 techers in Sintang and its surrounding areas. The method used is the descriptive method. The teachersâ€™ persception questionnaire on ICT in chemistry learning was addopted from Teachersâ€™ perception towards ICT in the teaching- learning process: Scale validty and reliability study were translated into Indonesian and modified to suit the conditions of the school. The results showed that the average perception of educators on the use of ICT in chemistry learning was 78,91 with a â€œGoodâ€ category, it is known that the use of ICT in chemistry learning is still not implemented for all educators